Does the World Need a Universal Financial Institution? - Boughton, James (Washington, D.C. : International Monetary Fund, 2005)
All financial institutions specialize, in dimensions that may include categories of assets and liabilities, types of services offered, customer demographics, and geographic coverage. The International Monetary Fund is the only international financial institution that is universal in its geographic scope, prepared to lend on request to virtually any country in the world. Why has this status come about? What are its costs and benefits? Is it an appropriate model for a world where macroeconomic imbalances, financial crises, and disparities in economic development must compete for attention and resources?.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet